Traditional practices versus modern healthcare: Determinants of traditional medicine use after potential dog bites among dog-owning households in Nigeria. - Philip P Mshelbwala; Kinley Wangdi; Jibrin Idris; Mohammad Mahmudul Hassan; Andrew M Adamu; Charles E Rupprecht; Nicholas J Clark (PLoS Neglected Tropical Diseases)
Canine rabies is endemic in Nigeria, with a low dog vaccination rate. Often, dog bite victims resort to traditional remedies, which can lead to fatalities. Our study investigated factors influencing decisions to seek traditional remedies in Nigeria. We conducted a cross-sectional study in 2022 involving 4,162 dog-owning households. A joint random effect Bayesian regression model was developed to examine the role of sociodemographic, socioeconomic, and infrastructural covariates. This model included a latent variable measuring a respondent's understanding of rabies risk based on literacy levels and responses to questions about rabies epidemiology. Our results indicated that 27% (95% Confidence Interval [Cl); 26-27) of respondents would preferably seek traditional remedies following a dog bite. Male respondents were 24% more likely than female respondents to seek traditional remedies (odds ratio [OR]: 1.24; 95%, Credible Interval CrI): 1.07-1.31). Similarly, individuals residing in rural areas reported 55% higher likelihood of using traditional remedies than those in urban areas (OR: 1.55; 95% CrI: 1.43-1.67). Respondents residing in areas with no veterinary services reported 35% higher likelihood of using traditional remedies than those near such facilities (OR: 1.35; 95% CrI: 1.15-1.42). Children under 16 years reported 27% lower likelihood of using traditional remedies than adults (OR: 0.73; 95% CrI: 0.49-0.84). Private or unemployed individuals were more likely to seek traditional remedies than civil servants (OR: 1.99; 95% Crl: 1.53-2.37). Respondents with tertiary education reported 42% lower likelihood of using traditional remedies than those without formal education (OR: 0.58; 95% CrI: 0.49-0.62). Our latent variable representing understanding of rabies risk was negatively associated with the probability of seeking traditional remedies (OR: 0.67; 95% CrI: 0.54-0.73). Lastly, poverty was negatively associated with the likelihood of seeking traditional remedies (OR: 0.78; 95% CrI: 0.66-0.82). Our findings provide important insights into healthcare behaviour decisions and their possible associations with rabies outcomes in Nigeria. These results highlight the need to improve public education, enhance access to medical care, and involve traditional healers in rabies prevention and control programs.